"You Need To Let Go of Control”: Critical Reflections of a Participatory Action Research Doctoral Project with Muslim Women in Britain - Akalu, Hanna (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2023)
This article explores the ethical and practical complexities of conducting participatory action research (PAR) as a doctoral student and shares findings from a doctoral study co-developed with Muslim women living in Britain to promote social change. Through the development of a visual methods (Photovoice) project, 16 Muslim women collaborated to document new understandings of what Muslim womanhood, religious agency, and empowerment mean to them, within the broader context of gendered Islamophobia. The findings reveal the complexities of establishing an equal partnership, and negotiating power dynamics, trust, ownership, and group conflict in PAR, which problematises assumptions around community empowerment within participatory approaches. The article concludes with critical reflections captured during the project, which advances understandings of how diverse Muslim women respond to PAR within the British context.